Cadence and workload effects on pedaling technique of well-trained cyclists - Rossato, M.; Bini, R. R.; Carpes, F. P.; Diefenthaeler, F.; Moro, A. R. P. (International Journal of Sports Medicine, 2008)
This study investigated the effects of changing cadence and workload on pedaling technique. Eight cyclists were evaluated during an incremental maximal cycling and two 30-minute submaximal trials at 60 % and 80 % of maximal power output (W60 % and W80 %, respectively). During submaximal 30-minute trials, they cycled for 10 minutes at a freely chosen cadence (FCC), 10 minutes at a cadence 20 % above FCC (FCC + 20 %), and 10 minutes at a cadence 20 % below FCC (FCC - 20 %). Pedal forces and kinematics were evaluated. The resultant force (RF), effective force (EF), index of effectiveness (IE) and IE during propulsive and recovery phase (IEprop and IErec, respectively) were computed. For W60 %, FCC - 20 % and FCC presented higher EFmean (69 ± 9 N and 66 ± 14 N, respectively) than FCC + 20 % (52 ± 14 N). FCC presented the highest IEprop (81 ± 4 %) among the cadences (74 ± 4 and 78 ± 5 % for FCC - 20 % and FCC + 20 %, respectively). For W80 %, FCC presented higher EFmean (81 ± 5 N) than FCC + 20 % (72 ± 10 N). The FCC - 20 % presented the lower IEprop (71 ± 7 %) among the cadences. The EFmin was higher for W80 % than W60 % for all cadences. The IE was higher at W80 % (61 ± 5 %) than W60 % (54 ± 9 %) for FCC + 20 % (all p < 0.05). Lower cadences were more effective during the recovery phase for both intensities and FCC was the best technique during the propulsive phase. see also: http://www.ufsm.br/gepec/ijsm2008.pdf